Transition Metal Assisting Pre‐Lithiation Reduces the P/N Ratio to Balance the Energy Density and Cycle Life of Aqueous Batteries. Issue 44 (22nd September 2022) - Lv, Tianshi; Zhu, Xiangzhen; Lin, Zejing; Suo, Liumin
Abstract: Aqueous Li‐ion batteries (ALIBs) are safe, environmentally friendly, and cost‐effective, promising for electric energy storage (EES). The high voltage ALIBs (HV‐ALIBs) supported by water‐in‐salt electrolytes are ideal for lowering the energy cost ($/Wh) of EES. However, HV‐ALIBs have been built with a high positive/negative capacity ratio (P/N ratio) to ensure their long‐term cycle life due to the irreversible Li consumption in the initial cycle induced by the solid electrolyte interface (SEI) formation and the parasitic reaction. Thus, the benefits of HV‐ALIBs in cost and energy density are mitigated inevitably. Generally, the feasible approach is adding per‐lithiation additives (PAs) to compensate for the capacity loss in the initial cycle. However, using PAs in ALIBs is challenging due to the high chemical activity of water. Here, a new strategy to achieve the pre‐lithiation by introducing manganese metal as a sacrificial PA for HV‐ALIBs that can provide over 900 mAh g −1 specific capacity without any adverse impact is proposed. The P/N ratio reduces to 1.02 by the LiMn2 O4 ||TiO2 pouch cell using the sacrificial manganese PA. This results in a high initial energy density above 120 Wh kg −1 and outstanding cycle stability with a capacity retention of 80% after 400 cycles. Abstract : Transition metal manganese is explored as the pre‐lithiation additive in aqueous lithium‐ion batteries by its oxidation in the initial cycle for the first time. The LiMn2 O4 ||TiO2 aqueous full cell with Mn as the pre‐lithiation additive delivers high energy density and better cycle performance than the non‐pre‐lithiation cell in a low P/N ratio.